Solving a hydrodynamic problem on a method of multipoint search in a distributed computing environment - Глазок, О. М.; Квач, М. М. (Problems of Informatization and Control, 2015)
The method of multipoint search for numerical solution of a hydrodynamic problem is offered. Theproblem of optimization of partition of calculation load between the nodets of the distributedcomputing environment at realization of this method is considered. The use of the offered methodallows to go round local minimums of the target function and optimize the use of computing resources